The Impact of Digital Learning Technologies on Students’ English Learning Strategies in the New Normal Era - Sakkir, Geminastiti; Atmowardoyo, Haryanto; Dollah, Syarifuddin (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study examines the impact of digital learning technologies on English learning strategies among secondary and tertiary students in the New Normal era, combining quantitative and qualitative perspectives. Quantitative data were collected from 206 English education university students via a Likert-scale questionnaire assessing technology use frequency, perceived usefulness, and learning strategy adoption. Qualitative data were gathered from senior high school students in South Sulawesi through an open-ended questionnaire on strategies, media, and study habits. Findings indicate that digital tools, particularly YouTube, Google Translate, online dictionaries, and mobile apps, are extensively used and perceived as beneficial across educational levels. Quantitative results show significant positive correlations between technology use and metacognitive, cognitive, and social-affective strategies. Regression analysis confirms that technology use and perceived usefulness predict strategy adoption. Qualitative findings reveal diverse student strategies such as independent study, media consumption, vocabulary memorization, and the use of both online and offline resources. The study concludes that digital technologies facilitate self-regulated, interactive, and resource-rich learning, offering pedagogical implications for technology-integrated language instruction in the post-pandemic era.